Evaluation of anti-plaque microbial activity of Azadirachta indica (neem oil) in vitro: A pilot study - Sugumari Elavarasu; P Abinaya; S Elanchezhiyan; Thangakumaran; K Vennila; K B Naziya (Wolters Kluwer Medknow Publications, 2012)
Background: Probably microbial plaque is the main etiology for periodontal tissue inflammation. Various chemical agents have been evaluated over the years with respect to their antimicrobial effects in the oral cavity. However, all are associated with side effects that prohibit regular long-term use. Therefore, the effectiveness of Azadirachta indica (neem) against plaque formation is considered to be vital, with lesser side effects. The aim of the present study is to evaluate and prove the antimicrobial activity of neem using plaque samples. Materials and Methods: Culture was prepared using brain heart infusion broth reagent. Dental plaque samples were used for that. Kirby-Bauer antimicrobial susceptibility test procedure was carried away with the sample. Neem oil was kept in the agar plate with culture and the diameter of inhibition zones was calculated. Results: Results showed inhibition zones on the agar plate around neem oil. Conclusion: Study shows definite antiplaque activity of neem oil.